2016
DOI: 10.1016/j.envres.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Urinary polycyclic aromatic hydrocarbons and measures of oxidative stress, inflammation and renal function in adolescents: NHANES 2003–2008

Abstract: Objective Recent evidence has suggested that polycyclic aromatic hydrocarbons (PAHs) may contribute to cardiometabolic and kidney dysfunction by increasing oxidative stress, but little is known about impacts in childhood. Study design We performed cross-sectional analyses of 660 adolescents aged 12–19 years in the 2003–2008 National Health and Nutrition Examination Survey (NHANES), using levels of 10 monohydroxylated urinary PAH metabolites as our exposure. Our primary outcomes of interest were biomarkers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 79 publications
2
52
2
Order By: Relevance
“…31, 32 Studies of other populations at levels more similar to those observed presently have detected associations with these and other oxidative stress biomarkers as well. 33, 34 In regard to pregnant women specifically, this is the first study to examine associations between urinary PAH biomarkers and 8-OHdG, 8-iso, and the tyrosine adducts during gestation. Another study of 2-NAP and 1-PYR reported associations with increases in malondialdehyde, another biomarker of oxidative lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…31, 32 Studies of other populations at levels more similar to those observed presently have detected associations with these and other oxidative stress biomarkers as well. 33, 34 In regard to pregnant women specifically, this is the first study to examine associations between urinary PAH biomarkers and 8-OHdG, 8-iso, and the tyrosine adducts during gestation. Another study of 2-NAP and 1-PYR reported associations with increases in malondialdehyde, another biomarker of oxidative lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…One study used a dipstick to measure proteinuria (Factor-Litvak et al, 1999). Among the studies that examined estimated glomerular filtration rate (eGFR), seven studies used creatinine based estimating equations (Fadrowski et al, 2010, Farzan et al, 2016, Garcia-Esquinas et al, 2013, Kataria et al, 2015a, Kooijman et al, 2015, Loghman-Adham, 1998, Watkins et al, 2013). Four studies used Cystatin C based estimating equations to determine eGFR (Fadrowski et al, 2010, Skroder et al, 2015, Hawkesworth et al, 2013, Filler et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…These include studies of fluoride levels(Xiong et al, 2007; Liu et al, 2005), aflatoxin (Hassan et al, 2006a) and ochratoxin (Hassan et al, 2006b), maternal smoking levels (Taal et al, 2011, Kooijman et al, 2015), secondhand smoking (Garcia-Esquinas et al, 2013), Bisphenol A, Triclosan, Benzophenone-3 (Trasande et al, 2013), PFOA (Geiger et al, 2013; Watkins et al, 2013; Kataria et al, 2015a), Bisphenol-A-glycidyl-dimethacrylate (bisGMA) (Trachtenberg et al, 2014), melamine exposure (Lam et al, 2008; Guan et al, 2009), polycyclic aromatic hydrocarbons (PAHs) (Farzan et al, 2016) and various phthalate compounds (Trasande et al, 2014, Tsai et al, 2016) (Table 3). The study designs included 12 cross-sectional, 1 case control, 2 prospective cohort, 1 retrospective cohort, and 1 randomized clinical trial.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore due to the complex nature of PAHs, high content excreted in urine can be associated with recent exposure, while low excretion is assigned to low exposure or decreased ability to detoxify a particular PAHs compounds [36]. However, high levels of urine PAH were also reported for adolescents aged 12-19 years following National Health and Nutrition Ex- EAHT amination Survey (NHANES) [37]. Abiodun et al, showed that PAHs pollution was more in Asia and Africa than elsewhere in the world [38].…”
Section: Eahtmentioning
confidence: 99%